2020
DOI: 10.1111/ejn.15017
|View full text |Cite
|
Sign up to set email alerts
|

Testing the effect of tACS over parietal cortex in modulating endogenous alpha rhythm and temporal integration windows in visual perception

Abstract: Neural oscillations in the alpha band (8-12 Hz) have been proposed as a key mechanism for the temporal resolution of visual perception. Higher alpha frequencies have been related to improved segregation of visual events over time, whereas lower alpha frequencies have been related to improved temporal integration. Similarly, also the phase of ongoing alpha has been shown to correlate with temporal integration/segregation. To test a causal relationship between alpha oscillations and perception, we here employed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(42 citation statements)
references
References 89 publications
0
42
0
Order By: Relevance
“…By comparing performance across these phase bins, they were able to explore whether a phase-specific modulation of performance emerged from their data. Even if they found preliminary evidence of a relation between integration accuracy and tACS phase, a more stringent permutation test did not confirm the strength of the effect ( Figure 4D) (Ronconi et al, 2020a). In sum, even if tACS was previously shown to shape detection accuracy in a sinusoidal fashion (Helfrich et al, 2014b;de Graaf et al, 2020), this study provides only partial evidence on whether tACS is able to effectively modulate segregation/integration performance in a phase-dependent manner.…”
Section: Temporal Binding Alpha Rhythm and Temporal Bindingmentioning
confidence: 56%
See 4 more Smart Citations
“…By comparing performance across these phase bins, they were able to explore whether a phase-specific modulation of performance emerged from their data. Even if they found preliminary evidence of a relation between integration accuracy and tACS phase, a more stringent permutation test did not confirm the strength of the effect ( Figure 4D) (Ronconi et al, 2020a). In sum, even if tACS was previously shown to shape detection accuracy in a sinusoidal fashion (Helfrich et al, 2014b;de Graaf et al, 2020), this study provides only partial evidence on whether tACS is able to effectively modulate segregation/integration performance in a phase-dependent manner.…”
Section: Temporal Binding Alpha Rhythm and Temporal Bindingmentioning
confidence: 56%
“…In line with the electrophysiological literature (for reviews see VanRullen, 2016;White, 2018), some studies also showed a phase-dependent modulation of accuracy and reaction times induced by occipital tACS in detection tasks (Helfrich et al, 2014b;de Graaf et al, 2020). Nonetheless, it should be noted that other studies using parietal tACS did not convincingly find consistent evidence in a task that directly measured both integration and segregation performance (Ronconi et al, 2020a). This study addressed possible issues concerning tACS effectiveness such as the choice of the stimulation montage and current distribution modeling that should be investigated more deeply in future studies to increase tACS efficacy in the exploration of visual temporal binding.…”
Section: Temporal Binding: Summarymentioning
confidence: 57%
See 3 more Smart Citations